Development of a Block Scheme of Optoelectronic Device for Control of Gas Concentration - Sultonov Shukhrat Davlyatovich (Zien Journals, 2023)
This article presents and describes the principle of operation of an optoelectronic device for monitoring the concentration of gases in biogas and geothermal combined plants based on a block diagram and timing diagrams.
Keywords: optoelectronics; semiconductor; radiation source